2009
DOI: 10.1002/mnfr.200800592
|View full text |Cite
|
Sign up to set email alerts
|

EGCG inhibits protein synthesis, lipogenesis, and cell cycle progression through activation of AMPK in p53 positive and negative human hepatoma cells

Abstract: In the previous studies, (-)-epigallocatechin-3-gallate (EGCG) has been shown to have anticarcinogenic effects via modulation in protein expression of p53. Using p53 positive Hep G2 and p53 negative Hep 3B cells, we found that treatment of EGCG resulted in dose-dependent inhibition of cellular proliferation, which suggests that the interaction of EGCG with p53 may not fully explain its inhibitory effect on proliferation. Caloric restriction (CR) reduces the incidence and progression of spontaneous and induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
75
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 46 publications
3
75
1
Order By: Relevance
“…Cells are arrested in G1, S and G2/M phases to prevent replication of damaged DNA or to prevent aberrant mitosis. Previous studies reported that EGCG blocked progression of the cell cycle at G1 phase in HCC lines (12), which is reportedly related to the activation of AMPK (12). However, we found that EGCG caused S phase but not G1 arrest in SMMC7721 cells (Fig.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Cells are arrested in G1, S and G2/M phases to prevent replication of damaged DNA or to prevent aberrant mitosis. Previous studies reported that EGCG blocked progression of the cell cycle at G1 phase in HCC lines (12), which is reportedly related to the activation of AMPK (12). However, we found that EGCG caused S phase but not G1 arrest in SMMC7721 cells (Fig.…”
Section: Discussionmentioning
confidence: 44%
“…EGCG inhibited the growth and metastasis of pancreatic cancer (7,8) and colorectal cancer (9), reduced the incidence of esophageal cancer (10) and improved the prognosis of breast cancer (11). It also inhibited the growth of HepG2 cells (12).…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, in addition to the improvement of metabolic disorders, activation of AMPK by EGCG also positively contributes to the prevention of hepatotumorigenesis because decreased AMPK activation is implicated in tumor development and therefore may be a tumor suppressor and a promising target for cancer chemoprevention (38). In fact, EGCG has been shown to inhibit lipogenesis and cellcycle progression through the activation of AMPK in human HCC-derived cells (39). The phosphorylation of LKB1, which is a tumor suppressor protein and a major AMPK kinase (38), is also increased by EGCG (37).…”
Section: Discussionmentioning
confidence: 99%
“…recently, aMPK was shown to be involved in cellular homeostasis and emerged as a pivot point between cell survival and apoptosis (16)(17)(18). Previous studies have reported that aMPK activation regulates apoptosis in cancer cells via a signaling pathway that includes the up-regulation of p53 protein, activation of caspases, generation of roS and inhibition of the proteolytic cleavage of poly (adP-ribose) polymerase (ParP)-lKB1 (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%